Kemandirian Keuangan, Rasio Efisiensi, Rasio Solvabilitas Anggaran dan Rasio Pertumbuhan terhadap Financial Distress Pemerintah Daerah - Lailiyah, Nur Isro’atul; Desitama, Faizal Satria (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study aims to prove empirically the effect of financial independence, efficiency ratio (level of capital outlay), budgetary solvency ratio, growth ratio to financial distress of district and city governments in East Java Province for the period 2018-2022. This research method uses a quantitative approach. The sampling technique is a saturated sample (total sampling) obtained from a total sample of 190 observed data from 29 districts and 9 cities multiplied by five years of the observed period. The data analysis technique in this study uses binary logistic regression analysis. The results showed that Financial Independence and Efficiency Ratio (LCO) had a significant negative effect in predicting financial distress conditions, while the budget solvency ratio (BSR) and growth ratio had no effect in predicting financial distress conditions. The independent variables in this study explain 62.5 percent of the dependent variable, while the remaining 37.5 percent is explained by variable factors outside the study that are not considered by the researcher.